2020
DOI: 10.3389/fmicb.2020.566613
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Root-Associated Bacteria That Influence Plant Physiology, Increase Seed Germination, or Promote Growth of the Christmas Tree Species Abies nordmanniana

Abstract: Abies nordmanniana is used for Christmas tree production but poor seed germination and slow growth represent challenges for the growers. We addressed the plant growth promoting potential of root-associated bacteria isolated from A. nordmanniana . Laboratory screenings of a bacterial strain collection yielded several Bacillus and Paenibacillus strains that improved seed germination and produced indole-3-acetic acid. The impact of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…s50 increased the seed germination rate and systemic resistance to pathogens while Paenibacillus sp. s37 increased plant root growth in both greenhouse and field conditions ( Garcia-Lemos et al, 2020 ). Similar to those found in PGP rhizobacteria, several fungal species such as Trichoderma virens are also known to produce indole-3-acetic acid and other auxin-related compounds to positively impact the growth and development of plants, including rice, cotton, and Arabidopsis ( Contreras-Cornejo et al, 2009 ).…”
Section: Plant Microbiomes Contribute To the Productions Of Psmsmentioning
confidence: 99%
“…s50 increased the seed germination rate and systemic resistance to pathogens while Paenibacillus sp. s37 increased plant root growth in both greenhouse and field conditions ( Garcia-Lemos et al, 2020 ). Similar to those found in PGP rhizobacteria, several fungal species such as Trichoderma virens are also known to produce indole-3-acetic acid and other auxin-related compounds to positively impact the growth and development of plants, including rice, cotton, and Arabidopsis ( Contreras-Cornejo et al, 2009 ).…”
Section: Plant Microbiomes Contribute To the Productions Of Psmsmentioning
confidence: 99%
“…Effect of SynCom application on plant growthThis study showed that the seed application of SynComs improved germination and early plant growth parameters. Enhanced germination percentage and rate in T1 treatments (SynCom-seed dressing) suggests that SynCom application helped to break seed dormancy, possibly by quickening metabolic processes(Garcia-Lemos et al, 2020;Rostamikia et al, 2016). Likewise, higher shoot growth parameters (7.4% higher shoot height and 5.1% higher shoot biomass) indicated that SynCom application at seedling stage can confer improved plant fitness at the early growth stage.…”
mentioning
confidence: 99%
“…We report the complete genome sequence of Paenibacillus sp. strain 37, previously isolated from the rhizosphere of Abies nordmanniana (Nordmann fir) seedlings sampled at Baumschule Engler, Hohenlockstedt, Germany (53°58′30.5″N, 9°37′51.9″E) ( 2 ). A single colony of strain 37 was inoculated in lysogeny broth (LB) overnight at 28°C, and genomic DNA (gDNA) was purified using the NucleoSpin kit (Macherey-Nagel, DE) according to the manufacturer’s instructions.…”
Section: Announcementmentioning
confidence: 99%